Hazy Boundaries: Virtual Communities and Research Ethics - Helena Kantanen; Jyri Manninen (Media and Communication, 2016)
This paper examines ethical issues specific to research into virtual communities. Drawing on an empirical case with online forums of education experts, we identify the following key issues: publicity versus privacy of the community; the definition of human subjects research; participant recruitment; informed consent; and ethical questions associated with observing virtual communities, and with reporting and disseminating research results. We maintain that different research cultures in different countries can present challenges when studying global forums. Acknowledging the ephemeral characteristics of Internet contexts, this paper argues that ethical considerations should be more case-based, instead of relying on one model for all solutions. We suggest that local ethics committees or institutional review boards could, with their expert knowledge of ethics, provide valuable support for researchers operating in the complex and dynamic terrain of Internet research, as well as in fields and research settings where an ethical review is not a standard part of the research process.